The Chinese species of the genus Phlaeopterus Motschulsky, 1853 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini) - Shavrin, Alexey V. (Zootaxa, 2020)
New combinations in the genus Phlaeopterus Motschulsky, 1853 for three Chinese species, originally described in Lesteva Latreille, 1797, are proposed: P. rufimarginatus (Rougemont, 2000) comb.n., P. ruzickai (Shavrin, 2015) comb.n., and P. septemmaculatus (Rougemont, 2000) comb.n. Phlaeopterus hromadkai Shavrin sp.n. from China (Gansu: Dalijia Shan) is described and illustrated. A list of species and a key to the Palaearctic species of Phlaeopterus are provided. The distributions of all Chinese species are mapped.